2012
DOI: 10.1007/s11695-012-0606-3
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Changes in Gastric Morphology and Histopathology Following Sleeve Gastrectomy in Diet-Induced Obese Rats

Abstract: After SG gastric macro- and microscopic changes with functional implications in both the short and long term take place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…In our study, SG rats had significantly greater weight loss from 15 days postoperatively compared with sham rats, and then weights increased in both groups but remained lower in SG rats compared with sham rats at 24 weeks postoperatively. These results have been reported previously in Wistar rats at 5 weeks [20] and 16 weeks after SG [21]. Interestingly, food intake became similar from 15 days postoperatively and remained the same at 24 weeks postoperatively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, SG rats had significantly greater weight loss from 15 days postoperatively compared with sham rats, and then weights increased in both groups but remained lower in SG rats compared with sham rats at 24 weeks postoperatively. These results have been reported previously in Wistar rats at 5 weeks [20] and 16 weeks after SG [21]. Interestingly, food intake became similar from 15 days postoperatively and remained the same at 24 weeks postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, food intake became similar from 15 days postoperatively and remained the same at 24 weeks postoperatively. These results have also been reported in rats at 5 weeks [20], 12 weeks [21], and 16 weeks after SG [21]. In humans, weight regain after SG is also often observed after 2 or 3 postoperative years, and it is always observed in studies with 10-or 15-years postoperative follow-up [14][15][16][17].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Concerning the residual gastric mucosa, it has been reported that cell proliferation increased and apoptosis was down-regulated in the excluded gastric mucosa of biopsies from RYGB-operated obese patients [ 44 ]. In the remaining fundus of the rat after VSG, changes in gastric morphology with gastric foveola elongation, hyperplasia and cystic dilatation of the glands were reported [ 45 ]. In our rat model, we did not observe such changes in gastric morphology after VSG but, we found the residual stomach (both fundus and antrum) dilated.…”
Section: Discussionmentioning
confidence: 99%
“…A duodenal switch consists of a vertical gastrectomy followed by bypassing a large portion of the small intestine (39). Noteworthy, animal studies have found contradictory findings regarding gastric sleeve morphology (35,40). From a histological point of view, the gastric mucosa undergoes changes with increased numbers of mucous neck cells and increased numbers of enlarged parietal cells.…”
Section: Gastrointestinal Acid Secretion After Sleeve Gastrectomy and Roux-en-y Gastric Bypassmentioning
confidence: 99%